Neuropathic pain in primary knee osteoarthritis patients: correlation with physical function, quality of life, disease severity, and serum beta nerve growth factor levels - Shereen R. Kamel (SpringerOpen, 2021)
Abstract Background Neuropathic mechanisms are thought to play a role in knee osteoarthritis (KOA) pain. Neuropathic pain questionnaires can promote diagnosis of a neuropathic component. Thus, we aimed to assess the frequency of neuropathic pain in primary KOA patients (using clinical questionnaires) and to investigate its correlation with socio-demographic factors, physical function, quality of life, disease severity, and serum beta nerve growth factor (β-NGF) levels. Results Seventy primary KOA patients were included. Neuropathic pain was detected in 52.9% of patients based on Douleur Neuropathique en 4 Questions (DN4) questionnaire and in 38.6% of patients based on Leeds assessment neuropathic pain symptoms and signs questionnaire (LANSS). Serum β-NGF levels were significantly higher in KOA patients than controls (P<0.0001), and in KOA patients with neuropathic pain compared with patients with non-neuropathic pain. DN4 score was positively correlated with Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain, stiffness, and physical function, and it was also negatively correlated with Osteoarthritis knee hip quality of life questionnaire (OAKHQOL) pain scores (r s =0.459, P<0.001; r s = 0.258, P= 0.031; r s = 0.307, P= 0.010; r s = −0.337, P= 0.004, respectively), while LANSS scale was positively correlated with symptom duration, WOMAC stiffness, Lequesne pain, and Lequesne index (r s= 0.260, P= 0.020; r s = 0.343, P= 0.004; r s = 0.344, P= 0.004; r s = 0.322, P= 0.007) and negatively correlated with OAKHQOL physical, OAKHQOL mental health, OAKHQOL social support, and total OAKHQOL scores (r s = −0.258, P= 0.031;r s = −0.254, P= 0.034; r s = −0.283, P= 0.018; r s = −0.261, P= 0.029 respectively). Conclusions Neuropathic pain symptoms are frequent in primary KOA patients. KOA patients with neuropathic pain have worse quality of life, extreme disability, and higher serum β-NGF levels. Nerve growth factor inhibitors could have a potential role for not only relieving pain in KOA patients but also improving functional disability and quality of life in these patients.